Facilitators and barriers influencing healthcare professionals’ productivity in Ethiopia: a phenomenological study - Jemal Mohammed Ali; Zeine Abosse; Firew Ayalew; Tegbar Yigzaw Sendekie; Shelemo Shawula; Trhas Tadesse; Fikadu Asrat; Mezgebu Yitayal; Jelle Stekelenburg (BMC Health Services Research, 2026)
Abstract Background Understanding the lived experiences of healthcare professionals is crucial for identifying the factors that impact their productivity. In most countries in sub-Saharan Africa, particularly in Ethiopia, despite efforts to improve the performance of the health workforce, there is a lack of qualitative insights into the specific deterrents and facilitators they encounter. Objectives This study explores the experiences of healthcare professionals in Ethiopia, focusing on the key factors that facilitate or hinder their productivity. It aims to provide insights into how healthcare professionals perceive influences on their work efficiency. Methods Using a phenomenological research design, we conducted in-depth and key informant interviews from July 1 to July 23, 2023, with purposively sampled healthcare providers and health leaders from hospitals across Ethiopia. Each hospital contributed one manager and two clinical staff members for the interviews. The data were analyzed using thematic analysis to uncover participants’ experiences related to productivity in healthcare facilities. Results A total of 30 healthcare providers and managers working in ten hospitals from eight regions and city administrations were interviewed. The study identified five key themes related to factors that facilitate or hinder productivity: capacity building, motivation and satisfaction, performance management, work climate, and absenteeism. The main facilitators of productivity included continuous professional development opportunities, access to mentoring and coaching support, non-financial incentives, efforts to enhance work environments, and communication. On the other hand, barriers primarily consisted of resource constraints, inadequate infrastructure, a lack of transparent decision-making related to promotion and recognition, a shortage of health professionals, and the absence of a standardized performance appraisal system. Employing a phenomenological approach allowed for a deeper understanding of how healthcare professionals experience and interpret these factors in their daily work. Conclusion Healthcare professionals in Ethiopia perceived productivity as closely linked to quality of care, patient outcomes, and efficient service delivery rather than quantitative measures alone. Productivity was facilitated by training, supportive supervision, mentorship, fair incentives, teamwork, and adequate resources. However, shortages of supplies and equipment, inadequate infrastructure, weak performance management systems, poor working conditions, absenteeism, and staff turnover negatively affected productivity. Addressing these organizational and system-level challenges through improved workforce support, motivation, infrastructure, and professional development may strengthen healthcare workforce productivity and retention in Ethiopia.